2021
DOI: 10.1111/jcmm.16377
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib suppresses self‐renewal and leukemogenesis of leukemia stem cell by NF‐ĸB‐dependent inhibition of CDK6 in MLL‐rearranged myeloid leukemia

Abstract: Acute myeloid leukaemia (AML) with chromosomal rearrangements involving the H3K4 methyltransferase mixed‐lineage leukaemia (MLL) is an aggressive subtype with low overall survival. Bortezomib (Bort) is first applied in multiple myeloma. However, whether bort possesses anti‐self‐renewal and leukemogenesis of leukaemia stem cell (LSC) in AML with MLL rearrangements is still unclear. Here, we found that bort suppressed cell proliferation and decreased colony formation in human and murine leukaemic blasts. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The authors demonstrated that bortezomib suppressed the self-renewal ability of LSCs by inhibiting the recruitment of NF-κB to Cyclin dependent kinase 6 (CDK6) promoter and consequently the expression of CDK6. Since bortezomib acts selectively against LSCs with little side effects againts normal HSPC, these studies supports the potential use of bortezomib in AML patients with MLL rearrangements [ 122 ].…”
Section: Nf-κb Core Pathway Inhibitorsmentioning
confidence: 59%
“…The authors demonstrated that bortezomib suppressed the self-renewal ability of LSCs by inhibiting the recruitment of NF-κB to Cyclin dependent kinase 6 (CDK6) promoter and consequently the expression of CDK6. Since bortezomib acts selectively against LSCs with little side effects againts normal HSPC, these studies supports the potential use of bortezomib in AML patients with MLL rearrangements [ 122 ].…”
Section: Nf-κb Core Pathway Inhibitorsmentioning
confidence: 59%
“…Bortezomib treatment has also been shown to increase the overall survival and reduce the self-renewal capacity of leukemic stem cells in mouse leukemic cells expressing MLL-AF9, a KMT2A fusion protein. The cell cycle regulatory protein kinase CDK6 has been demonstrated to be one of the important targets of bortezomib in myeloid-derived KMT2A-r leukemia 19 . The same study also showed that, mechanistically, the effect of bortezomib was mediated by the reduction in CDK6 expression by preventing the recruitment of NF-κ B to the CDK6 promoter.…”
Section: Discussionmentioning
confidence: 87%
“…The cell cycle regulatory protein kinase CDK6 has been demonstrated to be one of the important targets of bortezomib in myeloid-derived KMT2A-r leukemia. 19 The same study also showed that, mechanistically, the effect of bortezomib was mediated by the reduction in CDK6 expression by preventing the recruitment of NF-κ B to the CDK6 promoter. With respect to other potential mechanisms, quantitative mass spectrometry on KMT2A-r ALL protein samples treated with bortezomib resulted in the upregulation of proteins like ATF4, which is known to be involved in the endoplasmic reticulum (ER) stress-induced cell death.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite the large number of tests involving TKIs, medications and methodologies have also been developing as the case of Bortezomibe. Its function is based on decreasing the expression of CDK6, an important agent in the proliferation of LSCs (120,125,126).…”
Section: Treatment Perspectivesmentioning
confidence: 99%